Competency Test Preparation Assistance Indonesian Pharmacy Diploma Students 2024 - Wibowo, Teguh Setiawan (Institute Of Advanced Knowledge and Science, 2024)
Pharmacy is one of the health fields combined with the chemistry which is responsible for ensuring the effectiveness and safety of drugs. To maintain the quality of Indonesian Pharmacy optimally and better in the future, reliable pharmacists are needed who come from a pharmaceutical background, especially Diploma Pharmacy students. The purpose of the mentoring activity in preparing for Ujian Kompetensi Mahasiswa Diploma Farmasi Indonesia (UKMDFI) 2024 is to strengthen the Pharmacy materials that have been previously taught and ensure the students are well prepared to face the competency exam so they can pass and practice professionally. The methods used the theoretical material reinforcement sessions, discussions, practice questions and try out or exam simulation conducted on 284 Pharmacy Diploma students and held online via zoom meeting by Neuroacademy. The result is the community service through mentoring activities in preparing for Ujian Kompetensi Mahasiswa Diploma Farmasi Indonesia (UKMDFI) received a positive response and enthusiasm from the participants who attended. It is expected that graduates of the Diploma in Pharmacy can become professionals in the field of Pharmacy who can proven knowledge, technical skills, Pharmacy management and have a high awareness of the importance of working in accordance with the applicable standards and the quality.